Desempeño docente en la formación virtual de los estudiantes del cuarto y quinto ciclo en la Institución Educativa Pública Primaria N° 60066 Virgen de Lourdes, Yanashi 2022 - Diaz Flores, Monica del Pilar (2023)
In the present investigation, the general objectivehas been to describe the level of teaching performance in the virtual training of fourth and fifth cycle students in the Primary Public Educational Institution No. 60066 Virgen de Lourdes in the town of Yanashi in 2022. For this purpose, we worked with the type of descriptive research with a cross-sectional, field and univariate design as methodology. 136 students made up the populationand sample to whom, for data collection, a questionnaire previously validated by experts was applied, and through the survey technique. As a conclusion, the level of teaching performance in the virtual training of thestudents of the fourth and fifth cycle of the primary educational institution "Virgen de Lourdes" of Yanashi is high for 53.7% (n = 73) of the students. students, regular for 44.8% (n=61) and low for only 1.5% (n=2).